ANALISIS PERBANDINGAN TINGKAT EFISIENSI BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH DI INDONESIA DENGAN MENGGUNAKAN METODE STOCHASTIC FRONTIER ANALYSIS (SFA) PERIODE 2014-2016 - Vidia Tutik; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this study was to examine whether the Total Deposits,Operational costs, and other Operations costs affect the Total Financing and tofind out the analysis of the efficiency level of the Sharia Commercial Banks andSharia Business Units. The type of research used is quantitative to analyze theanalysis comparing the level of efficiency of Islamic Commercial Banks andSharia Business Units in Indonesia through using the Stochastic Frontier Analysis(SFA) rule for the period 2014-2016. Based on the results of the sample criteria,there were 11 companies sampled in the study including 5 Islamic BusinessEnterprises (BUS) and 6 Sharia Business Units (UUS).The results of the study used SFA indicated